2020
DOI: 10.1186/s12977-019-0510-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal within-host evolution of HIV Nef-mediated CD4, HLA and SERINC5 downregulation activity: a case study

Abstract: The HIV accessory protein Nef downregulates the viral entry receptor CD4, the Human Leukocyte Antigen (HLA)-A and-B molecules, the Serine incorporator 5 (SERINC5) protein and other molecules from the infected cell surface, thereby promoting viral infectivity, replication and immune evasion. The nef locus also represents one of the most genetically variable regions in the HIV genome, and nef sequences undergo substantial evolution within a single individual over the course of infection. Few studies however have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…We noticed that the chronic Env clones tend to be more resistant to SERINC5 than the T/F and acute Env clones. This may partly result from the accumulated polymorphisms in viral Nef protein over the long course of chronic infection, which impair the ability of Nef to counter SERINC5 (41). Partial loss of SERINC5 antagonism by Nef could lay more pressure on HIV-1 Env to resist SERINC5.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that the chronic Env clones tend to be more resistant to SERINC5 than the T/F and acute Env clones. This may partly result from the accumulated polymorphisms in viral Nef protein over the long course of chronic infection, which impair the ability of Nef to counter SERINC5 (41). Partial loss of SERINC5 antagonism by Nef could lay more pressure on HIV-1 Env to resist SERINC5.…”
Section: Discussionmentioning
confidence: 99%
“…SERINC5-iHA expression was increased when JTAg-SERINC3/5 −/− cells were transfected with DNA encoding SERINC5-iHA, whereas co-transfection with DNA encoding SERINC5-iHA and Nef SF2 -GFP resulted in substantial reduction in cell surface expression of SERINC5-iHA ( Fig. 4A), confirming Nef 's ability to downregulate SERINC5 23,36,37 . All patient-derived Nef clones tested were functional with respect to the SERINC5-iHA downregulation function, but the activity level was different to a relatively small extent within a host, but to a large extent across hosts (Fig.…”
Section: Functional Effects Of Nef Variants In the Context Of Patientmentioning
confidence: 65%
“…Recent reports demonstrated that three specific sites in Nef, the amino acids 12 to 39, the ExxxLL motif (S163C) and the AP-2 binding site (R178G), were identified to be involved in Nef function [ 14 , 15 , 16 , 24 ] ( Figure 1 ). In addition, multiple amino acid variations in Nef (subtype B HIV-1) were identified to play a role in SERINC3 and SERINC5 antagonism [ 14 , 25 , 26 ] ( Figure 1 ) including 8R, 9S, 11P, 12G, 14A/P/S, 15A, 21K/R, 28E, 43I, N51T, 54D, 63E, 81F, H116N, 120F, V148L/X, 157N, 158K, 161N, M168I/X, 182E and 188S, of which some specifically affected SERINC3 (8R, 9S, 11P, 12G, 14A, 15A, 21K, 28E, 43I, 182E and 188S) or SERINC5 (14S, 21R, 54D, 63E, 81F, 120F, 157N and 158K) [ 26 ]. We analyzed primary Nef proteins obtained from 123 individuals with HIV-1 participating in the Amsterdam Cohort Studies for amino acid changes at the previously described positions and regions as compared to consensus B ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%